2004
DOI: 10.1515/cclm.2004.112
|View full text |Cite
|
Sign up to set email alerts
|

Reference ranges for two automated chemiluminescent assays for serum insulin-like growth factor I (IGF-I) and IGF-binding protein 3 (IGFBP-3)

Abstract: Assays for insulin-like growth factor I (IGF-I) and IGF-binding protein 3 (IGFBP-3) have become essential tools in the diagnostic work-up of disorders of the somatotropic axis in children and adults. The aim of this study was to evaluate the automated IMMULITE IGF-I and IGFBP-3 assays and to establish reference limits--central 95% intervals, median, 0.1 and other centiles as clinically relevant--as a function of age from 797 females and 787 males, from the first week of life through the ninth decade. Pubertal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
189
4
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 258 publications
(220 citation statements)
references
References 7 publications
13
189
4
8
Order By: Relevance
“…The maximum difference in the upper limit (97.5th percentile) was 7 µg/L (20 to 30 years) and the maximum difference in the lower limit (2.5th percentile) was 10 µg/L (21 to 25 years). Therefore, similar to previous studies (7)(8)(9)(10)(11)(12)(13)(14), the IGF-1 reference values are reported according to age group, without distinction between genders ( Table 2). The curves representing the 97.5th, 50th (median) and 2.5th percentiles of IGF-1 as a function of age are shown in figure 1.…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…The maximum difference in the upper limit (97.5th percentile) was 7 µg/L (20 to 30 years) and the maximum difference in the lower limit (2.5th percentile) was 10 µg/L (21 to 25 years). Therefore, similar to previous studies (7)(8)(9)(10)(11)(12)(13)(14), the IGF-1 reference values are reported according to age group, without distinction between genders ( Table 2). The curves representing the 97.5th, 50th (median) and 2.5th percentiles of IGF-1 as a function of age are shown in figure 1.…”
Section: Resultssupporting
confidence: 79%
“…Ten groups divided according to age [5-year intervals (7,8)] were pre-defined, with 100 subjects per group (6,17). Since the need of different reference values for men and women is not clear (6), each group was divided into two subgroups (50 men and 50 women).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations